Pengaruh Minat dan Motivasi Belajar terhadap Hasil Belajar Matematika Siswa - Safitri, Dewi; Rochaminah, Sutji; Hasbi, Muh; Baharuddin, Baharuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to find: (1) the influence of learning interest on students' mathematics learning outcomes, (2) the influence of learning motivation on students' mathematics learning outcomes, and (3) the influence of learning interest and motivation on students' mathematics learning outcomes. This research was carried out at SMK Yadika Palu. Respondents totaled 139 people consisting of classes XI and XII and were determined using the Proportional Random Sampling technique. The method used is quantitative research with data collection techniques using instruments: (1) Learning Interest Questionnaire, (2) Learning Motivation Questionnaire, and (3) Student Mathematics Learning Outcomes Test. Data were analyzed using primary data obtained directly from students using simple regression analysis and multiple regression analysis. The results of the research show that: (1) There is an influence of Learning Interest on students' Mathematics Learning Outcomes of 3.9%, (2) There is an influence of Learning Motivation on students' Mathematics Learning Outcomes of 4.1%, and (3) There is an influence of Interest and Motivation Learning on student Mathematics Learning Outcomes is 4.2%. In conclusion, there is an influence of interest and learning motivation on students' mathematics learning outcomes which has a positive influence. Keywords: Learning outcomes; Interest; Motivation;